2021
DOI: 10.1177/00104140211024299
|View full text |Cite
|
Sign up to set email alerts
|

Why People Turn to Institutions They Detest: Institutional Mistrust and Justice System Engagement in Uneven Democratic States

Abstract: Does political mistrust lead to institutional disengagement? Much work in political science holds that trust matters for political participation, including recourse to the justice system. Scholars of judicial institutions, relying largely on survey research, argue that low trust decreases legal compliance and cooperation, threatening the rule of law. Legal consciousness and mobilization scholars, meanwhile, suggest that trust does not drive justice system engagement. However, their single-case study approach m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 62 publications
4
9
0
Order By: Relevance
“…Instead, Colombians have very high knowledge of human rights, and in the face of injustice and rights violations, engage in multiple forms of individual and collective action to demand the restoration of their rights. Engagement with state institutions to demand rights protections does not depend on socioeconomic status, gender, or race, even if women, displaced people, and lower-income Colombians recognize the system as biased in favor of the wealthy (Hilbink et al 2022). This rights consciousness and willingness to engage the system was an important driver for the National Strike resulting from the convergence of the health, socioeconomic, and governability crisis as the following section will show.…”
Section: The Third Crisis: Governabilitymentioning
confidence: 97%
See 3 more Smart Citations
“…Instead, Colombians have very high knowledge of human rights, and in the face of injustice and rights violations, engage in multiple forms of individual and collective action to demand the restoration of their rights. Engagement with state institutions to demand rights protections does not depend on socioeconomic status, gender, or race, even if women, displaced people, and lower-income Colombians recognize the system as biased in favor of the wealthy (Hilbink et al 2022). This rights consciousness and willingness to engage the system was an important driver for the National Strike resulting from the convergence of the health, socioeconomic, and governability crisis as the following section will show.…”
Section: The Third Crisis: Governabilitymentioning
confidence: 97%
“…Recent scholarship has shown that a lack of trust in institutions does not drive engagement with political, judicial, and other systems. Rather, citizens' deci-sion to participate in politics and engage with political institutions is driven by their expectations of the state (Kruks-Wisner 2018; Boulding and Holzner 2021;Hilbink et al 2022). This is especially the case in Colombia, where citizens have high levels of consciousness and knowledge of human rights, even among marginalized groups (Gallagher et al 2019;Hilbink et al 2022).…”
Section: Perspectives For the Futurementioning
confidence: 99%
See 2 more Smart Citations
“…In this article, we offer insights on these matters from an original, nationally representative (telephone) survey conducted at the height of a "broad and allencompassing" sociopolitical mobilization (Ansaldi and Pardo-Vergara 2020) in Chile, a stable democracy in which, aside from elections, political participation was limited, de jure by a rigid constitution that entrenched neoliberalism and established a minimal state and de facto by persistent and severe inequality (Corvalán and Cox 2013;Couso 2011;de la Maza 2014;Posner 2008;UNDP 2014). Chilean citizens were socialized to fend for themselves or to seek help from private sources (Araujo and Martuccelli 2012), and scholars have found that they exhibit limited knowledge and capacities to claim rights (Hilbink et al 2022). Then, in October 2019, mass protests against inequality, discrimination and sociopolitical exclusion erupted across the nation, lasting for several weeks.…”
mentioning
confidence: 99%